Is true informed consent achievable? - Matz, Miya (My University, 2022)
Imagine you have just found out that a loved one, such as a parent, sibling, or close friend, suffers from a rare and deadly genetic disorder. There are currently no successful mainstream treatments for this disorder. However, the doctor mentions a highly experimental treatment that would involve removing bone marrow from a healthy donor once a month for a full year and could potentially cause permanent damage to them. It turns out that you are a match. How would you make your decision regarding treatment? Most individuals would suggest leaving it to the doctor’s discretion, but because it is your body, it is ultimately your choice. You attempt to do further research on the internet but end up confused and frustrated. How will you ultimately decide as to whether you should give informed consent for the procedure?
Keywords: informed consent; medical procedures